Is the Decision Not to Use Contraception an Indicator of Reproductive Agency?. Issue 1 (15th February 2023) - Fabic, Madeleine Short; McDougal, Lotus; Raj, Anita; Jadhav, Apoorva
Abstract: Women's engagement in the decision to use contraception, an indicator captured in the Demographic and Health Surveys (DHS), is frequently used to assess women's reproductive agency. In 2014, DHS added a corollary question to the women's questionnaire on decision‐making not to use contraception. Study authors hypothesize that women's engagement in decision‐making not to use contraception is also indicative of reproductive agency. Analyzing DHS microdata from 30 countries collected between 2015 and 2020 ( n = 292, 141), this country‐level study examines data quality in terms of missingness of data ( t ‐tests), indicator utility in terms of response pattern variability (descriptive statistics), and construct validity in terms of associations between engagement in the decision not to use contraception and engagement in household decision‐making (multivariable linear regression). Findings indicate the measure is of good quality, provides nuanced insight, and has construct validity. Importantly, the new measure deepens our understanding of women's reproductive agency.